MEDIA PEMBELAJARAN PROPAGASI LINE OF SIGHT PADA MATA KULIAH ANTENA DAN PROPAGASI DI S1 PENDIDIKAN TEKNIK ELEKTRO UNDIKSHA - mutammam, muhammad; Nyoman Santiyadnya; I Putu Suka Arsa (Jurnal Pendidikan Teknik Elektro Undiksha, 2023)
This research aims to: 1) create a Line of Sight Propagation Learning Media, 2) determine the feasibility of the Line of Sight Propagation Learning Media for the "Antenna and Propagation" course, 3) assess students' responses to the Line of Sight Propagation Learning Media. This study falls under the category of Research and Development (R&D). In this research, statistical data analysis was conducted, including the percentage of feasibility, to process the questionnaire data filled out by content experts and media experts. Data collection was carried out through questionnaires filled out by content experts, media experts, and students. The results of the research are as follows: 1. Validation by media experts showed a 75% feasibility percentage with a qualification of "feasible." 2. Validation by content experts showed an 87.5% feasibility percentage with a qualification of "highly feasible." 3. The results of the small-group test with five respondents indicated a "very high" category. 4. The results of the large-group test with fifteen respondents also indicated a "very high" category. Based on the findings of this research, it can be concluded that the Line of Sight Propagation Learning Media is suitable for use in the teaching process of the "Antenna and Propagation" course in the Electrical Engineering Education undergraduate program at Undiksha University.